Zinc Finger Proteins: Epigenetic Breakthroughs and Possible Treatment of Neurodegenerative Disorders - and Nidhi Tyagi, Manoj G. Tyagi*, (Recent Research in Science and Technology, 2010)
Engineered zinc finger proteins (ZFN) that bind specific DNA targets provide the foundation for a new class of technologies that promise significant gains in the development of novel therapeutics and molecular research tools. Individual zinc fingers have been developed in vitro to recognize many DNA triplets. When fused to the nonspecific DNA cleavage domain of the FOK1 restriction endonuclease, zinc fingers can direct double strand breaks to disrupt specific genes. Expanded triplet repeats have been identified as the genetic basis for a growing number of neurological disorders. Thus ZFN show promise for the treatment of monogenic disorders by promoting the knockout or correction of specific genes.